Analisis Beban Kerja Mahasiswa Praktikum Parasitologi Di Program Studi Ilmu Kesehatan Masyarakat Universitas Negeri Manado - Suarjana, I Wayan Gede (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 6 No 1 (2020): Volume 6 No 1 Juni 2020, 2020)
Teaching and learning process at Public Health Studies Program at Manado State University was hoped can be carried out well not only in theory but at practical activity. One of the practicum that was carried out was parasitology practicum. Practical activities carried out for 4 to 5 hours. At the end of the practicum, students often experience symptoms such as feeling sore, stiff and tired and the lab accuracy was not good. This condition need to be corrected to the activities carried out during carrying out the practicum, especially from the workload of students. Therefore, a descriptive experimental study was carried out by the observational method to all students of Grade A semester IV enrolled in the parasitology practicum courses. The number of student were 25 students. The workload analysis was done by measurements of heart rate, environment conditions, subjective fatigue, musculoskeletal disorders and Extra Calorie due to Peripheral Temperature (ECPT) and Extra Calorie due to Peripheral Metabolism (ECPM). The environment factors measured is dry temperature, wet temperature, relative humidity, light intensity, and noise. The results of the study show that the workload of students is moderate category that requires further intervention. There is a significant increase in subjective fatigue and musculoskeletal disorders before and after practicum. Because of ECPM is greater than ECPT, it is necessary to improve working conditions related to student physical activity that refers to the rules of ergonomics, improvement of work posture, adjustment the time of practicum and rest time, adjusting practicum equipment in according with student anthropometry, and controlling work environment.